SUB CLASS OF HARMONIC UNIVALENT FUNCTIONS WITH INTEGRAL OPERATOR - Nagalaxmi Nakeertha,V. Srinivas (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
This paper introduced a new class of harmonic univalent function defined by an integral operator. Additionally study investigates some properties of this subclass such as essential as well as adequate coefficient bounds, extreme points, distortion bounds and hadamard product.